The Psychology of Food Cravings in Patients With First-Episode Psychosis - Kim, Young-Hyuk; Ryu, Seunghyong; Nam, Hee-Jung; Kim, Mina; Jhon, Min; Lee, Ju-Yeon; Kim, Jae-Min; Shin, Min Ho; Chung, Young-Chul; Kim, Sung-Wan (Frontiers in Psychiatry, 2020)
Objectives: Food cravings may cause weight gain in patients with schizophrenia. This study investigated psychological characteristics associated with food cravings in patients with first-episode psychosis. Methods: This study analyzed data from a clinical cohort of first-episode psychosis patients taking antipsychotics for 3 months or less. The strength of food cravings was measured using the General Food Cravings Questionnaire-Trait (G-FCQ-T). Psychological characteristics were investigated with the Positive and Negative Syndrome Scale (PANSS), Calgary Depression Scale for Schizophrenia (CDSS), Social and Occupational Functioning Assessment Scale, Rosenberg Self-Esteem Scale (RSES), and Perceived Stress Scale (PSS). G-FCQ-T data were analyzed according to status regarding significant weight gain over 3 months (≥ 10% increase in bodyweight compared to baseline). We also conducted gender-stratified analyses. Results: In total, 182 patients (78 males and 104 females) with first-episode psychosis were enrolled in this study. In females, the G-FCQ-T total score at baseline was associated with baseline bodyweight, significant weight gain over 3 months, and scores on the CDSS and PSS. Furthermore, the score on the loss of control G-FCQ-T subscale was significantly associated with the PANSS general, CDSS, PSS, and RSES scores. In males, a significant association was found only between the loss of control subscale and RSES scores. Conclusion: These results indicate that the food cravings of patients with first-episode psychosis, which is associated with weight gain, are influenced by psychological factors, particularly in females. To reduce food cravings in female patients with schizophrenia, interventions aimed at depression, stress, and low self-esteem should be considered.